1994
DOI: 10.1038/sc.1994.87
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cortical magnetic stimulation in spinal cord injury

Abstract: Cortical magnetic stimulation was performed in a consecutive series of 10 patients presenting within 15 days of traumatic spinal cord injury. In those patients with complete paraplegia or quadriplegia, motor evoked potentials at presentation were absent below the level of the lesion. Six months after the injury, potentials had returned in the biceps brachii and abductor pollicis brevis muscles in some quadriplegic cases, but remained absent from the tibialis anterior in all of this group. None of those with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…Latency measurements of motor evoked potentials (MEP) after transcranial (tc) and lumbosacral (ls) magnetic nerve stimulation proved to be useful for distinguishing between peripheral and central corticospinal motor conduction disturbances [Merton and Morton, 1980;Cowan et al, 1984;Barker et al, 1985;Ingram et al, 1988;Eisen, 1992;Clarke et al, 1994;Curt et al, 1998]. By application of electrical or magnetic stimuli to the motor cortex or to peripheral nerves electrophysiological activity of the target muscle can be elicited and the amplitude and latency of these evoked potentials can be measured [Caramia et al, 1989;Dvorak et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Latency measurements of motor evoked potentials (MEP) after transcranial (tc) and lumbosacral (ls) magnetic nerve stimulation proved to be useful for distinguishing between peripheral and central corticospinal motor conduction disturbances [Merton and Morton, 1980;Cowan et al, 1984;Barker et al, 1985;Ingram et al, 1988;Eisen, 1992;Clarke et al, 1994;Curt et al, 1998]. By application of electrical or magnetic stimuli to the motor cortex or to peripheral nerves electrophysiological activity of the target muscle can be elicited and the amplitude and latency of these evoked potentials can be measured [Caramia et al, 1989;Dvorak et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MMEPs in rats are typically reported to not correlate with basic locomotion tests; 15 however, MMEP studies in human SCI patients found high sensitivities of MMEPs for spinal integrity and functional outcome. [16][17][18] Hence, the backward locomotion test seems to correlate with long tract function, which has translational value for locomotion function in humans.…”
Section: Discussionmentioning
confidence: 99%
“…By combining magnetic stimulation of cortical and peripheral nervous structures (spinal roots, plexus, peripheral nerves), lesions of spinal and/or peripheral nerves underlying a muscle paresis can be di erentiated. 16,17 Sympathetic skin response (SSR) The sympathetic skin response (SSR) is a simple and non-invasive electrophysiological test to examine the common e erent pathways of the sympathetic nervous system. Pathways from the spinal cord to the sudomotor sweat glands of hands (palmar), feet (plantar) and the perineal skin region transmitted by pre-and post-ganglionic sympathetic nerve ®bres can be evaluated.…”
Section: Motor Evoked Potential (Mep)mentioning
confidence: 99%